Polychlorinated biphenyls in the ambient air of petroleum refinery, urban and rural areas - Lee, Wen-Jhy; Lin Lewis, Sue J.; Chen, Ying-Yuan; Wang, Ya-Fen; Sheu, Hwey-Lin; Su, Chun-Ching; Fan, Yi-Chin (Atmospheric environment (1994), 1996)
PCB samples in the ambient air of petroleum refinery (PR), urban and rural areas have been collected by several PS-1 samplers from October 1992 to April 1993 at southern Taiwan. Both total-PCBs and PCB-homologues associated with concentration, phase distribution, particle-bound composition and dry deposition were investigated. Mean total-PCB concentrations in the ambient air were found to be 5.02, 4.75, and 2.61 ngm −3 for PR, urban, and rural area, respectively. This result indicated that PCB concentrations in the ambient air were possibly correlated with industrial and/or human activities. The patterns of PCB homologues were quite similar with the distribution of those found in the mixture of Aroclor 1242 and 1260. Mean gas-phase distributions of total-PCBs were 63.1, 63.1, and 50.7% in PR, urban, and rural area, respectively. For PCB emission sources, the extent to which PCBs enter the ambient air was probably controlled by gas phase. Total-PCB compositions in all those three areas were quite similar, being 11.3, 11.2 and 9.87μg g −1 in PR, urban, and rural area, respectively. PCB-homologue distributions of particle-phase samples were quite similar to those found in Aroclor 1260. The calculated dry deposition velocity, V d, of total-PCBs averaged 0.88, 0.39 and 0.68 cm s −1 for the PR, urban and rural site, respectively. These V d are similar to those measured or estimated by previous studies. The calculated mean dry deposition velocities of PCB homologues among these three sampling sites were 0.27, 0.48, 0.60, 0.77, 0.93, 0.89 and 0.88 cm s −1 for the di-, tri-, tetra-, penta-, hexa-, hepta- and octa-CBs, respectively. In general, the dry deposition velocities increased as chlorination of PCB homologue increased. This is due to the fact that the low chlorination PCB homologues are enriched in the gas phase. Dry deposition of gas-phase PCBs is mainly by diffusion and has lower dry deposition velocities. Higher chlorinated PCB homologues, primarily associated with the particles phase, are deposited mostly by gravitational settling. The dry deposition velocities caused by gravitational settling are much higher than those by diffusion.